ANALISIS KEWAJIBAN PELAPORAN SPT TAHUNAN PPh ORANG PRIBADI DAN KONTRIBUSI TERHADAP PENERIMAAN PPh (STUDI PADA WAJIB PAJAK PENSIUNAN DI KPP PRATAMA MALANG UTARA) - Pritalangeni, Dila Ayu (Jurnal Mahasiswa Perpajakan, 2014)
Directorate General Of Taxation has conducted intensification and extensification of tax as measure to raise the number of tax ratio in Indonesia. The Government started combing the retirees to increase tax revenues. This study aimed to identify and explain the effectiveness of the annual income tax return for individual taxpayer retirees and the contribution toward to income tax revenue. The research is qualitative research. Data collection techniques used interview method, documentation and triangulation. Data analysis tool is Miles and Huberman interactive model The result of this study show percentage of the effectiveness of reporting annual tax return individual tax income for retirees taxpayers was 63,33% so that the rate effectiveness of retired taxpayers said â€œenough effectiveâ€ if counted based on scale of measurement the effectiveness. The contribution income tax of retired taxpayers has the contribution was still â€œlessâ€ result of contribution criteria is which only reached average 0,73%. Keywords: SPT the individual income tax,Â  Retired Taxpayer, Income Tax.